LESS COMMON PATTERNS WITH INTENSIFIERS ‘TOO’ AND ‘VERY IN THE CORPUS OF INUGURAL ADDRESSES OF US PRESIDENTS - Prihantoro, Prihantoro (Universitas Pendidikan Indonesia, 2015)
Â AbstractThis paper studies â€œveryâ€ and â€œtooâ€, two intensifiers used in the corpus of inaugural address of all US presidents, from Washington to Obama. My aims here is to identify uncommon pattern with â€œtooâ€ and â€œveryâ€, and the semantic prosodies as well. I downloaded the data and processed it as a corpus by using a corpus tookit called AntConc (Anthony, 2006). I used the query â€œveryâ€ and â€œtooâ€ to obtain concordances. A shared feature of these intensifiers is they mostly modify adjectives as shown by frequency. Although less significant in terms of frequency, some common patterns are discovered, such as â€œvery + Nâ€ and â€œvery + AdjSuperlative + Nâ€ construction, which are attested in COCA. One that is against prescriptive grammar is a + too + Adj + Nâ€, where the suggested construction is usually â€œtoo + Adj + a + Nâ€. As for the semantic prosody, I found some data attested in COCA, where â€œtooâ€ can be used to intensify positive evaluation, which is contrary to Azar (2002) and some other grammar books. As for very, it is more flexible that the prosodies might either be positive or negative. The result of COCA and BNC has shown that these structures are uncommon. I argue that these structures are used under the markedness frame, to make listeners focus on issues that the speakers wanted to empahasize.Keywords: very, too, intensifiers, semantic prosody, inaugural address, corpusÂ AbstrakArtikel ini menyelidiki